Field-scale evaluation of a solar-powered double-nozzle venturi aeration system for water quality management in tilapia cage culture - Thoharudin; Sunardi; Fitroh A.K. Yudha; Muhammad Nadjib; Aqiel Z. A. Pudjianto (Jurnal Teknik Mesin Indonesia, 2026)
Freshwater aquaculture requires efficient and affordable aeration to maintain water quality, especially in stagnant or low-circulation waters where dissolved oxygen (DO) depletion can reduce fish survival and productivity. This study evaluated the field-scale performance of a solar-powered double-nozzle Venturi bubble generator for nighttime aeration in a large tilapia floating cage. The system was installed in an 11 m × 17 m cage containing about 6000 tilapia and used eight double-nozzle Venturi aerators driven by a 12 V DC pump with an off-grid photovoltaic-battery supply. It operated intermittently from 00:30 to 08:30 using a 30 min ON/30 min OFF cycle, equivalent to 4 h day⁻¹ of effective operation. Each unit produced an average water flow of 6.73 L min⁻¹ and air entrainment of 1.12 L min⁻¹, while the pump consumed 63.12 W. A minimum battery capacity of 449.28 Ah was required and met by a 500 Ah battery bank, while the photovoltaic system was adequately sized for local solar conditions. Field results showed stable pH (6.7–7.3), while DO became the main limiting factor. Aerated water maintained 4.5 mg L⁻¹ DO compared with 3.8 mg L⁻¹ in non-aerated water, confirming the system’s feasibility and effectiveness for off-grid tilapia cage culture.